2004
DOI: 10.1182/blood-2003-08-2864
|View full text |Cite
|
Sign up to set email alerts
|

Donor treatment with pegylated G-CSF augments the generation of IL-10-producing regulatory T cells and promotes transplantation tolerance

Abstract: We investigated whether the protection from graft-versus-host disease (GVHD) afforded by donor treatment with granulocyte colony-stimulating factor (G-CSF) could be enhanced by dose escalation. Donor treatment with human G-CSF prevented GVHD in the B6 → B6D2F1 murine model in a dose-dependent fashion, and murine G-CSF provided equivalent protection from GVHD at 10-fold lower doses. Donor pretreatment with a single dose of pegylated G-CSF (peg-G-CSF) prevented GVHD to a significantly greater extent than standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 53 publications
10
102
0
Order By: Relevance
“…27,28 There are also data suggesting that GCSF-induced protection against acute GVHD may be mediated through NK cells 29 and recently it has been shown that CD4 þ T cells exposed to GCSF may acquire the properties of regulatory cells that can prevent GVHD. 30,31 The increased rates of chronic GVHD observed in our PBSC compared to BM recipients following identical nonmyeloablative conditioning are in keeping with several reports of a high incidence of chronic GVHD after myeloablative PBSCT. 3,5,23,32,33 Possible explanations for the increased incidence of chronic GVHD following PBSCT include the larger numbers of CD34 þ cells and T cells in the infused inoculum [34][35][36][37][38] and the skewed cytokine profile, namely polarization of donor T cells toward a Th2 phenotype.…”
Section: Discussionsupporting
confidence: 71%
“…27,28 There are also data suggesting that GCSF-induced protection against acute GVHD may be mediated through NK cells 29 and recently it has been shown that CD4 þ T cells exposed to GCSF may acquire the properties of regulatory cells that can prevent GVHD. 30,31 The increased rates of chronic GVHD observed in our PBSC compared to BM recipients following identical nonmyeloablative conditioning are in keeping with several reports of a high incidence of chronic GVHD after myeloablative PBSCT. 3,5,23,32,33 Possible explanations for the increased incidence of chronic GVHD following PBSCT include the larger numbers of CD34 þ cells and T cells in the infused inoculum [34][35][36][37][38] and the skewed cytokine profile, namely polarization of donor T cells toward a Th2 phenotype.…”
Section: Discussionsupporting
confidence: 71%
“…Further evidence in favor of a role for G-CSF in the promotion of Treg cell differentiation stems from studies in mice demonstrating that treatment with pegylated G-CSF augments the generation of IL-10-producing Treg cells and promotes transplantation tolerance (36). Pegylated G-CSF-mediated protection from graft-vs-host disease (GVHD) was crucially dependent on IL-10 production by T cells.…”
Section: Induction Of Treg Cells By G-csfmentioning
confidence: 99%
“…19 Animals with severe clinical GVHD (scores Ն 6) were killed according to ethical guidelines, and the day of death was deemed to be the following day, as previously described. 12,16,17,20 Statistics Survival curves were plotted using Kaplan-Meier estimates and compared by log-rank analysis. The Mann Whitney U test was used for the statistical analysis of cytokine data and clinical scores.…”
mentioning
confidence: 99%